Globalizing oil firms and oil market governance in France, Japan, and the United States - Hughes, Llewelyn 1971- (Business and public policy., 2014)
"Oil is the world's most important commodity. It is also its most politicized. Yet in Globalizing Oil Llewelyn Hughes shows that since the 1970s governments across the advanced industrial states liberalized oil markets by freeing prices, lowering trade barriers, and privatizing national oil companies. How did this come about? And why do some governemnts continue to intervene in support of domestic firms? In answering these questions, Hughes shows that the transformation of the international oil market in the 1970s changed the risks and opportunities facing firms. He also shows their ability to benefit was conditioned by previous attempts to shape the competitive landscape. Changes in oil market governance in the 1980s and 1990s can thus be understood as a temporal process, in which institutional legacies affected firm sstrategies towards liberalization. Hughes' study has important implications not only for the politics of oil, but also for the study of economic liberalization." -- Book jacket.